Plastic pollution in agricultural landscapes: an overlooked threat to pollination, biocontrol and food security - Sheng, Dong; Jing, Siyuan; He, Xueqing; Klein, Alexandra-Maria; Köhler, Heinz-R.; Wanger, Thomas C. (Nature communications, 2024)
Ecosystem services such as pollination and biocontrol may be severely affected by emerging nano/micro-plastics (NMP) pollution. Here, we synthesize the little-known effects of NMP on pollinators and biocontrol agents on the organismal, farm and landscape scale. Ingested NMP trigger organismal changes from gene expression, organ damage to behavior modifications. At the farm and landscape level, NMP will likely amplify synergistic effects with other threats such as pathogens, and may alter floral resource distributions in high NMP concentration areas. Understanding exposure pathways of NMP on pollinators and biocontrol agents is critical to evaluate future risks for agricultural ecosystems and food security. Ecosystem services such as pollination and biocontrol are affected by increasing plastic pollution with potential implications for food security. Here the authors synthesize the little known effects of nano- and microplastics on pollinators and biocontrol agents at the organismal, farm and landscape scale.